PERSEPSI MASYARAKAT TERHADAP TRADISI BALIMAU KASAI DI DESA KUAPAN KECAMATAN TAMBANG KABUPATEN KAMPAR - Arman, Fajri; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village yawning Mining District of Kampar regency. The aim of this study is to Know the procession shower balimau kasai according to custom in the village yawning Kampar District of Mine. This study, entitled "Public Perception Of Tradition In the village yawning Balimau Kasai Mining District of Kampar regency". Topics focus of this research is how the procession shower balimau kasai according to the tradition in the village yawning Kampar District of Mine. The informants are all citizens who live in the village of yawning. While the sampling is the purposive sampling. Where sampling is done because the researcher selects the entire population of the village community are all yawning. Samples taken as many as 5 people from the whole community that is in the location of the research, the author uses qualitative descriptive method and the data was analyzed qualitatively. Data instrument is observation, interview, and documentation. The results showed Privileged Balimau Kasai is a custom event containing sacred values are typical. Travelers who followed the event can watch Kampar and surrounding communities flocked to the riverbank (Sungai Kampar) to perform the ritual bath together. Before people throw themselves into the river, bathing ritual begins with a meal shared by the public often referred eat majamba Balimau Bakasai it is the designation for a ceremony welcoming the arrival of the holy month of Ramadan in a way drenched-Mandian that aims to purify ourselves from sin during this time we do since the release of Ramadan last year. However, the event which was originally used as purification changed the meaning of the scene find a mate and shower as a couple who are not unrelated. Balimau Kasai used as the last day before the day everything is forbidden on the next day. we as young people have to straighten this custom because it has smudged will disrepute.Keywords: Balimau kasai, Balimau Cultural Values kasai